PENGARUH PENGGUNAAN MEDIA SOSIAL DALAM SUDUT PANDANG LANDASAN SOSIOLOGI TERHADAP POLA PIKIR SISWA SMKN 2 PELAIHARI SEBAGAI GENERASI Z - Purnamasari, Indah; Prasetyo, Muhammad Arief; Muzdalifah, Elva; Aslamiah, Aslamiah; Amelia, Rizky (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
This study aims to analyze the influence of social media use on the mindset formation of Generation Z students at SMKN 2 Pelaihari from the perspective of the foundations of educational sociology. This study is motivated by the phenomenon of massive digitalization, which has positioned social media as a dominant agent of socialization, thus triggering a shift in students' values ??and critical thinking skills amidst an instant culture. Using a descriptive quantitative method, data were collected through a Likert-scale questionnaire from 90 respondents selected through proportional random sampling. The instrument test results showed very good validity with an average score of 3.72. Empirical findings revealed that the intensity of students' social media use is high, with the majority of respondents (42.6%) accessing digital platforms for more than 8 hours per day. Specifically, the critical thinking indicators for the aspects of social problem analysis and information evaluation reached the high category with average scores of 3.89 and 3.76, respectively. However, the aspect of social impact reflection remained in the medium category with an average score of 3.41. The main conclusion of the study confirms that social media significantly shapes new habitus for students, so strengthening sociology education is crucial to bridge the gap between digital information analysis skills and reflective social value awareness. ABSTRAK Penelitian ini bertujuan menganalisis pengaruh penggunaan media sosial terhadap pembentukan pola pikir siswa SMKN 2 Pelaihari sebagai Generasi Z ditinjau dari perspektif landasan sosiologi pendidikan. Studi ini dilatarbelakangi oleh fenomena masifnya digitalisasi yang menempatkan media sosial sebagai agen sosialisasi dominan, sehingga memicu pergeseran nilai dan kemampuan berpikir kritis siswa di tengah budaya instan. Menggunakan metode kuantitatif deskriptif, data dikumpulkan melalui kuesioner berskala Likert dari 90 responden yang dipilih melalui teknik proportional random sampling. Hasil uji instrumen menunjukkan validitas sangat baik dengan skor rata-rata 3,72. Temuan empiris mengungkapkan bahwa intensitas penggunaan media sosial siswa tergolong tinggi, di mana mayoritas responden (42,6%) mengakses platform digital lebih dari 8 jam per hari. Secara spesifik, indikator pola pikir kritis pada aspek analisis masalah sosial dan evaluasi informasi mencapai kategori tinggi dengan nilai rata-rata masing-masing 3,89 dan 3,76, namun aspek refleksi dampak sosial masih berada pada kategori sedang dengan rata-rata 3,41. Simpulan utama penelitian menegaskan bahwa media sosial secara signifikan membentuk habitus baru bagi siswa, sehingga penguatan pendidikan sosiologi sangat krusial untuk menjembatani kesenjangan antara kemampuan analisis informasi digital dengan kesadaran nilai sosial yang reflektif.